Communicative approach and the teaching of speaking skill - Noraien Mansor; Mohd. Jalani Hasan (Penerbit Universiti Malaysia Terengganu, 2015)
Communicative Approach also known as Communication Language Teaching is an approach to foreigh or second language teaching which emphasizes that the goal of language learning is communicative competence. This book focuses on the effectiveness of using communicative approach in the learning of English Language specifically in the teaching of speaking skill via a module developed bu the author. DRA (Diagnose, Run and Access) Module consists of activities and strategies with communicative approach principles and characteristics to aid the instructors and students to enhance their speaking skill.